Bibliometric Analysis Commind Relax Support on Anxiety Among Pre Operative Patients - Setiaprabhawa, Farenzi Budi; Pranata, Satriya; Samiasih, Amin (Babali Nursing Research, 2023)
Background: Intervention in the management of anxiety is an approach that is currently being developed by researchers in various countries. This research needs the latest information and trends for future research topics related to cognitive behavior therapy interventions, mindfulness, relax, and support for anxiety in preoperative patients. Purpose: The purpose of this study was to determine the mapping of network visualization, overlay visualization, and density visualization using the VOSviewer application on the topic of the influence of cognitive behavior therapy, mindfulness, relax, and support (commind relax support) on the anxiety of preoperative patients. Methods: Data analysis used bibliometrics in this study. Search data using the web via http://app.dimensions.ai. Journals or data are limited from 2017-2023, which focus on the fields of health sciences, nursing, clinical sciences, public health, and types of publications are articles. The data is analyzed to become a bibliometric map using VOSviewer. Results: The results of data identification through dimensions.ai contained 24,099 data recorded, by sorting based on the type of article and type of document the results found were 645 articles. The peak of publications on cognitive behavior therapy, mindfulness, relax, and support for preoperative anxiety occurred in 2020 and the lowest was in 2023. Research on cognitive behavior therapy, mindfulness, relax, and support for preoperative anxiety is not only carried out in the health sector , medicine, nursing, and psychology but are found in other fields as well. Conclusion: The topic of preoperative anxiety management interventions is a topic that needs to be further developed in various countries, especially in developing countries. Suggestions for other researchers, choose a topic that is included in low visualization to find research updates.